Toll-Like Receptor 7 Activation Enhances CD8+ T Cell Effector Functions by Promoting Cellular Glycolysis - Li, Qian; Yan, Yan; Liu, Jia; Huang, Xuan; Zhang, Xiaoyong; Kirschning, Carsten; Xu, Haifeng C.; Lang, Philipp A.; Dittmer, Ulf; Zhang, Ejuan; Lu, Mengji (Frontiers in Immunology, 2019)
The activation of TLR7 signaling in T cells accelerates antigen-specific responses. Such responses play an essential role in eliminating viral infections and can be anti-tumorigenic. However, the underlying mechanisms of how TLR7 can promote the optimal function of CD8+ T cells remain unclear. To investigate how TLR signaling directly contributes to CD8+ T cell functions, we examine the activation of cellular TLR7-related pathways and functional and metabolic alterations in TLR7-stimulated T cells during T cell receptor signaling. In the present study, we investigated the activation of CD8+ T cells in response to direct stimulation by TLR7 ligands. TLR7 stimulation could promote the effector functions of purified CD8+ T cells in vitro. The TLR7-induced activation of CD8+ T cells occurs if CD8+ T cells were primed by αCD3 activation and increasingly expressed TLR7. MyD88and AKT-mTOR signaling plays a critical role in TLR7-induced T cell activation. In addition to the upregulation of immune-related genes, metabolic alterations in CD8+ T cells, including the upregulation of glucose uptake and glycolysis, occurred by TLR7 stimulation. Glycolysis was found to be regulated by the AKT-mTOR pathway and a downstream transcription factor IRF4. Blocking glycolysis by either direct glucose deprivation or modulating the mTOR pathway and IRF4 expression was found to impair T cell activation and functions. Taken together, the activation of TLR7 signaling promotes the effector functions of CD8+ T cells by enhancing cellular glycolysis.